2021
DOI: 10.1061/(asce)hy.1943-7900.0001857
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Durability of a Friction-Reducing Surface with Recoverable Superhydrophobicity

Abstract: The durability of super-hydrophobic surfaces in fully immersed conditions is a major obstacle to their application in engineering applications. We perform an experimental study to measure the friction factor f d as a function of time for a new super-hydrophobic surface that is capable of recovering the Cassie-Baxter wetting state. Values of f d were obtained by measuring the pressure drop and volume flux of a turbulent water flow in a 1.5 metre long duct containing one super-hydrophobic wall. The Reynolds numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, the major obstacle to the successful application of the coating in engineering applications is the durability and integrity of the coating without flakes of the hydrophobic substance being peeled off by the drag of the fluid flow. Some research works have focused on the durability of superhydrophobic surfaces in fully immersed conditions 24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the major obstacle to the successful application of the coating in engineering applications is the durability and integrity of the coating without flakes of the hydrophobic substance being peeled off by the drag of the fluid flow. Some research works have focused on the durability of superhydrophobic surfaces in fully immersed conditions 24 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Watanabe et al (Watanabe et al, 1999) reported that a 14% drag reduction was achieved for a laminar flow of water in a pipe with highly water-repellent wall. Other research works focused on the durability of superhydrophobic surfaces in fully immersed conditions that is a major obstacle to their use in engineering applications (Auwerter Liliane C. C. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%